2022
DOI: 10.3389/fenvs.2022.1076506
|View full text |Cite
|
Sign up to set email alerts
|

Limited role of shifting cultivation in soil carbon and nutrients recovery in regenerating tropical secondary forests

Abstract: Shifting cultivation is a dominant land-use in the tropical forest-agriculture frontier in Southeast Asia and is blamed for much of the environmental degradation in the region. We examined the distribution and availability of four soil macronutrients—i.e., soil organic carbon (SOC), total nitrogen (N), phosphorus (P) and potassium (K), in secondary forests regenerating after shifting cultivation abandonment. Soil samples were collected along an upland fallow gradient on Leyte Island in the Philippines. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 97 publications
0
2
1
Order By: Relevance
“…The initial differences of soil quality may influence farmers' land use decision and leads to a bias of the space-for-time approach used in our study (a negative trend of SOC stock across forest successional gradients). However, recent studies have suggested that soil fertility recovers to 90% of oldgrowth forest values within 10 years of land abandonment from agriculture activities (Poorter et al, 2021), and the highest rate of soil no-change (Bruun et al, 2021), gain (Gogoi et al, 2020) and loss (Sugihara et al, 2019) or fluctuation with fallow age (Chan et al, 2016;Mukul et al, 2022), but SOC tends to recover rapidly during the first 2 years of a fallow period (Lungmuana et al, 2017). Our models did not detect significant direct effects of forest succession on SOC stock (Figure 4).…”
Section: Soil Organic Carbon Stock and Forest Successioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The initial differences of soil quality may influence farmers' land use decision and leads to a bias of the space-for-time approach used in our study (a negative trend of SOC stock across forest successional gradients). However, recent studies have suggested that soil fertility recovers to 90% of oldgrowth forest values within 10 years of land abandonment from agriculture activities (Poorter et al, 2021), and the highest rate of soil no-change (Bruun et al, 2021), gain (Gogoi et al, 2020) and loss (Sugihara et al, 2019) or fluctuation with fallow age (Chan et al, 2016;Mukul et al, 2022), but SOC tends to recover rapidly during the first 2 years of a fallow period (Lungmuana et al, 2017). Our models did not detect significant direct effects of forest succession on SOC stock (Figure 4).…”
Section: Soil Organic Carbon Stock and Forest Successioncontrasting
confidence: 69%
“…However, recent studies have suggested that soil fertility recovers to 90% of old‐growth forest values within 10 years of land abandonment from agriculture activities (Poorter et al, 2021), and the highest rate of soil carbon sequestration occurs during the first 15 years (Bautista‐Cruz & del Castillo, 2005). Scientists hypothesized that SOC stock increases with forest age (Powers & Marín‐Spiotta, 2017), but evidence from field studies on shifting cultivation systems varies and includes no‐change (Bruun et al, 2021), gain (Gogoi et al, 2020) and loss (Sugihara et al, 2019) or fluctuation with fallow age (Chan et al, 2016; Mukul et al, 2022), but SOC tends to recover rapidly during the first 2 years of a fallow period (Lungmuana et al, 2017). Our models did not detect significant direct effects of forest succession on SOC stock (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Cecilio Rebola et al 2021;Mukul et al 2022;Primo et al 2023), highlighting the potential of AFSs to restore functional aspects in the Amazon. The practice of burning plant residues and the use of mineral fertilizers may have contributed to the increase in soil acidity over time, as these practices reduce soil pH and favor the release of hydrogen ions (H+) and aluminum (Al + 3) (Chaves et al 2020).…”
mentioning
confidence: 99%